2018
DOI: 10.1097/mpg.0000000000001799
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Exposure of Children to a Mixed Lipid Emulsion Is Less Hepatotoxic Than Soybean‐based Lipid Emulsion

Abstract: Lipid emulsions have been associated with liver injury. Newer mixed emulsions (ML), such as SMOFlipid (Fresenius Kabi, Germany), are thought to be more hepatoprotective than soybean-based emulsions (SL), such as Intralipid (Baxter). Pediatric studies comparing long-term use between the 2 are limited. This study compares the severity of hepatic injury between a prospective cohort of hospitalized children on ML (n = 20) and a historical age- and diagnosis-matched cohort of hospitalized children on SL (n = 20). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Lipid emulsions containing fish oil offer several potential advantages compared with lipid emulsions derived purely from soybean oil, including decreased ω‐6 and increased ω‐3 PUFA content, higher α‐tocopherol levels, and reduced phytosterol content . Studies in PN‐dependent infants and children at risk for IFALD have shown that multi‐component lipid emulsions containing fish oil reduce the risk of cholestasis and improve biochemical measures of hepatobiliary function compared with soybean lipid emulsions …”
Section: Pediatric Patients Requiring Pnmentioning
confidence: 99%
“…Lipid emulsions containing fish oil offer several potential advantages compared with lipid emulsions derived purely from soybean oil, including decreased ω‐6 and increased ω‐3 PUFA content, higher α‐tocopherol levels, and reduced phytosterol content . Studies in PN‐dependent infants and children at risk for IFALD have shown that multi‐component lipid emulsions containing fish oil reduce the risk of cholestasis and improve biochemical measures of hepatobiliary function compared with soybean lipid emulsions …”
Section: Pediatric Patients Requiring Pnmentioning
confidence: 99%
“…There have been efforts to prevent or reverse cholestasis by modifying lipid administration in patients requiring long‐term PN. Modifications include lipid minimization, temporarily discontinuing lipids, and using lipid emulsions containing lipid sources other than soybean oil (eg, pure fish oil or composite lipid emulsions with or without fish oil) …”
Section: Lipid Emulsions’ Role In the Treatment And Prevention Of Chomentioning
confidence: 99%
“…Because long‐term use of a pure soybean oil emulsion is a risk factor for cholestasis, both lipid restriction and the use of alternative lipid sources are potential preventative strategies . Studies evaluating the effect of lipid emulsions on the prevention of cholestasis in infants and children are shown in Table …”
Section: Lipid Emulsions’ Role In the Treatment And Prevention Of Chomentioning
confidence: 99%
See 2 more Smart Citations